Comparison of the Trilogy of Imam Ath-Thabarānī's Works: Al-Mu'jam Al-Kabīr, Al-Mu'jam Ash-Shaghīr and Al-Mu'jam Al-Awsath (Analysis of Compilation Methodology) - Rakhmat Fitrah Ramdhani; Milzam Priambodo; Rizzaldy Satria Wiwaha; Dadah; Mohamad Anton Athoillah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This paper analyzes the trilogy of mu'jam by Imam Abū al-Qāsim Sulaimān bin Aḥmad ath-Thabarānī (260–360 H): Al-Mu'jam al-Kabīr, Al-Mu'jam al-Awsath, and Al-Mu'jam ash-Shaghīr. This study uses a library method and a hadith science approach through a comparison of primary sources of study, namely the three ath-Thabarānī trilogies as canonical sources of hadith that complement the treasury of hadith science, then supported by various books related to hadith science as secondary sources of research. The focus of the study includes the methodology of compilation, the character of the curation of the narration, and the comparative value of the three for hadith studies—especially access to sanad verification and mapping of transmission paths which aim to understand the contents of each Mu’jam and analyze its function and contribution to sanad verification and path studies. Methodologically, al-Kabīr is arranged according to the musnad of the companions alphabetically (starting with Khulafā' Rāshidīn, then 'asyarah al-mubashsharūn), thus facilitating the consolidation of all narrations per companion. Al-Awsath is organized by the names of the teachers (shuyūkh) of Thabarānī and functions as a